Metabolic syndrome components and colorectal adenoma in the CLUE II cohort - Tsilidis, Konstantinos K (2009)
BACKGROUND: Metabolic syndrome components have been associated with colorectal cancer in several studies; however, the evidence for colorectal adenomas is limited. Thus, we evaluated the association between markers of the metabolic syndrome with colorectal adenoma development in a nested case-control study. METHODS: Colorectal adenoma cases (n= 132) and matched controls who had had a negative sigmoidoscopy or a colonoscopy (n=260) were identified between baseline in 1989 and 2000 among participants in the CLUE II cohort of Washington County, Maryland. Concentrations of C-peptide, insulin-like growth factor binding protein-1, glycosylated hemoglobin, total cholesterol, high density lipoprotein-cholesterol, and triglycerides were measured in baseline blood specimens. Body mass index was calculated using baseline height and weight. Use of medications to treat diabetes mellitus was self-reported at baseline. Blood pressure was measured at baseline. Distributional cutpoints of the latter markers were used to define the metabolic syndrome components (hyperinsulinemia, hyperglycemia, obesity, dyslipidemia, and hypertension) present at baseline. RESULTS: No statistically significant associations with adenomas were observed for the markers of the metabolic syndrome, with the exception of a strong positive association for use of diabetes medications (OR, 8.00; 95% CI, 1.70 – 37.67), albeit based on small numbers. CONCLUSION: Our findings do not support that components of the metabolic syndrome influence risk of colorectal adenomas, except possibly for severe diabetes mellitus warranting medical treatment.